Novel menadione hybrids: Synthesis, anticancer activity, and cell‐based studies. (21st August 2017) - Prasad, Chakka Vara; Nayak, Vadithe Lakshma; Ramakrishna, Sistla; Mallavadhani, Uppuluri Venkata
Abstract : A series of novel menadione‐based triazole hybrids were designed and synthesized by employing copper‐catalyzed azide‐alkyne cycloaddition (CuAAC). All the synthesized hybrids were characterized by their spectral data ( 1 H NMR, 13 C NMR, IR, and HRMS). The synthesized compounds were evaluated for their anticancer activity against five selected cancer cell lines including lung (A549), prostate (DU‐145), cervical (Hela), breast (MCF‐7), and mouse melanoma (B‐16) using MTT assay. The screening results showed that majority of the synthesized compounds displayed significant anticancer activity. Among the tested compounds, the triazoles5 and6 exhibited potent activity against all cell lines. In particular, compound6 showed higher potency than the standard tamoxifen and parent menadione against MCF‐7 cell line. Flow cytometric analysis revealed that compound6 arrested cell cycle at G0/G1 phase and induced apoptotic cell death which was further confirmed by Hoechst staining, measurement of mitochondrial membrane potential (ΔΨm) and Annexin‐V‐FITC assay. Thus, compound6 can be considered as lead molecule for further development as potent anticancer therapeutic agent. Abstract : Menadione‐based triazole hybrids were synthesized by employing copper‐catalyzed azide‐alkyne cycloaddition (CuAAC). The synthesized compounds were evaluated for their anticancer activity against five selected cancer cell lines. Compound6 showed higher potency than the standard tamoxifen and parent menadione against MCF‐7 cell line, arrested cell cycle at G0/G1 phase, and induced apoptotic cell death.